Karakteristik Kesejahteraan Psikologis Dan Kadar Gula Darah Pada Penderita Diabetes Mellitus - Putri Silvi; Darwin Karim; Musfardi Rustam (JUKEJ : Jurnal Kesehatan Jompa, 2023)
Diabetes mellitus is a metabolic disorder disease characterized by increased blood sugar levels due to decreased insulin secretion by pancreatic beta cells and/or impaired insulin function (insulin resistance). This study aims to describe the psychological well-being and blood sugar levels in people with diabetes mellitus. This research is a quantitative research using descriptive method to make an objective picture of a situation. The sample of this study amounted to 74 respondents using the technique purposive sampling. This study used a standard psychological well-being questionnaire and used a glucometer to measure blood sugar levels. The data analysis used is a simple descriptive form of a frequency distribution table. The results of this study indicate that 31 respondents (41,9%) accept their own state, 8 respondents (10,8%) have positive relationships with other people, 6 respondents (8,1%) have independence, 25 respondents (33,8%) can manage the environment, 2 respondents (2,7%) have a purpose in life, and 2 respondents (2,7%) have personal growth. People with diabetes mellitus with high psychological well-being are able to accept their situation, like undergoing the process of diabetes mellitus treatment, and are able to master the environment.